2020
DOI: 10.5747/ca.2020.v16.n4.a382
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição espacial de atributos do solo na região de El Oro, Equador

Abstract: The objective of this study was to generate information through the analysis of variability and given structure of spatial dependence as well as the linear correlation of physical and chemical attributes of the soil, in order to assist in the planning of agricultural activities in six cities in the province of El Oro, Ecuador. The soil sample collections were carried out every two kilometers in the form of a grid with smallchanges in the field with a Dutch-type auger and GPS for georeferencing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…Considering the data presented in Table 1, values of 1.85 dag kg -1 on average for organic matter in the soil were identified in the SSP-FEBN. Barbieri (2020), got organic matter values similar to this work (1.83 dag kg -1 ), which may be related, as both locations are located in an environment classified as tropical forest. Macronutrient P has its classes categorized as low (< 8 mg dm -3 ), medium (8 to 12 mg dm -3 ), and high (> 12 mg dm -3 ) according to Skorupa and Manzatto (2019).…”
Section: Descriptive and Geostatistical Analysis Of Soil Nutrientssupporting
confidence: 83%
See 1 more Smart Citation
“…Considering the data presented in Table 1, values of 1.85 dag kg -1 on average for organic matter in the soil were identified in the SSP-FEBN. Barbieri (2020), got organic matter values similar to this work (1.83 dag kg -1 ), which may be related, as both locations are located in an environment classified as tropical forest. Macronutrient P has its classes categorized as low (< 8 mg dm -3 ), medium (8 to 12 mg dm -3 ), and high (> 12 mg dm -3 ) according to Skorupa and Manzatto (2019).…”
Section: Descriptive and Geostatistical Analysis Of Soil Nutrientssupporting
confidence: 83%
“…However, Barbieri (2020) and Bamboriya et al (2022) indicated that pH in soils with a range between 6.0 and 6.8 showed cultures with higher productivity. Thus, with pH values found in Table 1, it is possible to identify, in general, that the soil in the work area has a more acidic pH than ideal.…”
Section: Descriptive and Geostatistical Analysis Of Soil Nutrientsmentioning
confidence: 97%
“…Os maiores fragmentos do mapa foram predominantemente compreendidos entre 0 a 0.8 g/kg -1 e de 0.8 a 1.6 g kg -1 (Figura 2f). Barbieri et al (2020) também encontraram resultados semelhantes na avaliação da variabilidade espacial em Neossolos embora outros trabalhos mostram que os valores de carbono para a mesma classe de solos avaliadas estão altos (VANSHCHENKO et al, 2007;MARTINS et al, 2019). Desta forma, o sistema de preparo na área estudada pode ter contribuído para a redução do COT, pelo aumento na taxa de decomposição da matéria orgânico (Freitas et al, 2018).…”
Section: Parâmetrosunclassified